Appraising Public Value in the Public Sector: Re-evaluation of the Strategic Triangle - Bojang, Malang B.S. (SEISENSE (PRIVATE) LIMITED, 2021)
Purpose- This article aims to address public value by assessing public programs and services' success in a more cost-effective way. The study also investigates how public managers and elected officials can use public value to guide their decisions on resource allocation to create value for the citizens. Design/methodology- To meet this study's aims, Mark Moore’s strategic triangle is used as the framework for this study. This is a comprehensive framework that evaluates the performance of public sector programs and service delivery. Data for this study has been collected via a primary scoping of the literature on public value. Database searches were conducted in the Social Sciences Index, SCOPUS journals, ISI Social Sciences Citation Index, and Google Scholar. Findings- From the investigation, the result indicates that public value is created by government or public managers in their daily transactions and by non-profit organizations that articulate their objectives and find popular support for the community's common good. Practical implications- Arguably, public value management provides a necessary improvement to public management theories. It redefines the function of public sector managers in the provision of socially desirable outcomes through citizen engagement. As a progress appraisal tool in public organizations, it offers a broader and inclusive framework than the New Public Management (NPM). Originality/value- This study's results contribute to the knowledge and literature of public value in the public sector. The strategic triangle builds on the challenges and weaknesses of NPM and it aims at reshaping institutions to prioritize value creation for citizens.